Energy efficiency potential determination for an oil treatment and stabilization unit at the field - Leonid M. Ulyev; Mikhail N. Chernyshov (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The desire to increase the energy efficiency of industrial enterprises and reduce greenhouse gas emissions from their activities. Reducing specific energy consumption at large oil refineries and petrochemical plants is not new and is quite widely used. Dozens of monographs and thousands of articles are devoted to these areas. But it should be taken into account that in the oil refining industry, all crude oil, even that which does not reach the refinery, necessarily passes through oil preparation and stabilization units at the fields. Therefore, in order to create energy-efficient and environmentally friendly processes throughout the entire oil refining chain, it is necessary to increase the energy efficiency of the oil preparation and stabilization units located at the fields. There are very few research works on thermal energy integration of oil preparation and stabilization units. Aim. Determination of target design and energy values for an energy-efficient retrofit project of the heat exchange network for the surveyed oil preparation and stabilization units and of its energy efficiency potential. Methods. Pinch analysis methods are used to determine the target values of an energy-efficient retrofit project. Mathematical modeling of heat exchange processes in the heat exchange network and economic analysis were performed using the Pinch 2.02 software; the Aspen HYSYS software package was used to create a simulation engineering model of the oil preparation and stabilization units. Results. When determining the target values of the heat exchange network retrofit project, the cost of energy and heat exchange equipment, the cost of collectors for splitting process streams, and technical restrictions on the placement of heat exchanger sections were taken into account. The inclusion of fuel gas in the process stream table has allowed the definition of target parameters for the optimal unit heat exchange network design to evolve. In the process of evolution of target values, the energy efficiency potential of the surveyed oil preparation and stabilization units was determined, which shows the possibility of reducing specific energy consumption by 77%. Upon implementation of the heat exchange network retrofit project and achievement of target parameters, the following economic results will be obtained: IRR=42%, NPV=7425780 USD, DPP 4 years. Also, CO2 emissions can be reduced by 30 thousand tons per year. It should be noted that the evolution of target designation and all target values for the reconstruction project were obtained before the implementation of the heat exchange network oil preparation and stabilization units project itself.